Hydrological Modelling and the Water Cycle Coupling the Atmospheric and Hydrological Models - Sorooshian, Soroosh; Hsu, Kuo-lin; Coppola, Erika; Tomassetti, Barbara; Verdecchia, Marco; Visconti, Guido (Water Science and Technology Library, 2008)
This collected work reports on the state of the art of hydrological model simulation, as well as the methods for satellite-based rainfall estimation. Mainly addressed to scientists and researchers, the contributions have the structure of a standard paper appearing in most cited hydrological, atmospheric and climate journals. Several already-known hydrological models and a few novel ones are presented, as well as the satellite-based precipitation techniques. As the field of hydrologic modeling is experiencing rapid development and transition to application of distributed models, many challenges including overcoming the requirements of compatible observations of inputs and outputs are addressed. The many contributing authors, who are well established in this field, provide readers with a timely overview of the ongoing research on these topics. The level of interest and active involvement in the discussions clearly demonstrate the importance the scientific community places on challenges related to the coupling of atmospheric and hydrologic models.